UPAYA KEPALA MADRASAH DALAM MENINGKATKAN MUTU KEGIATAN BELAJAR MENGAJAR (KBM) DI MI SYARIF ABBAS KABUPATEN TANAH BUMBU TAHUN PELAJARAN 2025/2026 - Taufik Ismail; Iskandar Zulkarnain; Dewi Yanti (UNISAN JURNAL, 2025)
This research was conducted to describe and analyze the various efforts undertaken by the Madrasah Principal to improve the quality of Teaching and Learning Activities (KBM) at MI Syarif Abbas, Tanah Bumbu Regency, in the academic year... Improving the quality of teaching and learning activities is a crucial aspect of education delivery, as the success of learning depends heavily on the effectiveness of the principal’s management and leadership. In this context, the madrasah principal plays a strategic role as a manager, leader, innovator, and motivator, responsible for creating a conducive learning environment, improving teacher competency, and ensuring the availability of adequate facilities and infrastructure. This research used a qualitative descriptive approach, with data collection techniques including observation, in-depth interviews, and documentation. The results indicate that the Principal of MI Syarif Abbas has undertaken various efforts to improve the quality of teaching and learning activities, including through planned and ongoing academic supervision, teacher professional development, motivation and rewards, and strengthening a culture of discipline and responsibility. Furthermore, the madrasah principal also provides learning resources, facilitates teacher training, and encourages the use of innovative learning strategies to improve the quality of the learning process and student learning outcomes. These efforts have had a positive impact on the quality of learning, as evidenced by improved teacher discipline, improved learning materials, increased creativity in teaching, and improved student learning outcomes. Therefore, it can be concluded that effective leadership by the madrasah principal is crucial for the success of improving the quality of teaching and learning at MI Syarif Abbas, and therefore requires continued development to achieve a quality educational institution.